Chaotic motion of a nonlinear near resonance centrifuge. (November 2020) - Guo, Feng; Li, Na
The equilibrium point and stability of the motion equation of the nonlinear near resonance centrifuge is studied, and the critical conditions for chaotic motions of the system under external excitation are studied by Melnikov method. The expression of Melnikov function and the boundary value between chaotic and non-chaotic regions are given. According to the range of parameters, the numerical simulations are carried out. The results show that the critical parameters of chaotic motion determined using Melnikov method are consistent with that obtained by the numerical simulation. This method effectively judges the occurrence of chaotic motion.